LAW ENFORCEMENT AGAINST PERPETRATORS OF CHILD SEXUAL VIOLENCE - Jannah, Lintang Nur; Apriliyanti, Apriliyanti; Febriana, Deby Wulandari; Hidayat, Dudung; Rasta, Gunadi (International Journal of Social Service and Research, 2024)
The definition of abuse (violence) is not only interpreted physically, but also mentally and even passively (neglect). It can be known, it is undeniable that on the other hand, Abuse in its implementation cannot be separated from the element of violence. Violence can be interpreted as wrong treatment, cruel treatment. In this regard, the problem is: how to enforce the law against sexual violence against children and how obstacles are to the implementation of law enforcement against sexual violence against children. The method used in this study uses a normative juridical method, namely research that focuses on finding legal norms, legal principles and legal doctrines to answer the legal issues to be studied. The results of this study found that the form of law enforcement used in this case uses a preventive method which prevents a person from committing a criminal act for the first time and also in the implementation of law enforcement there are still inhibiting factors that make the implementation of this law enforcement not run optimally, namely internal factors and external factors. Therefore, professional law enforcement is needed and also who can involve other stakeholders so that this law enforcement can run better.